"Justice-Oriented Legal Reasoning in Agrarian and Ecological Conflicts: A Critical Study of the Wadas Village Case" - Anggraeni, Puspita (Jurnal Locus Penelitian dan Pengabdian, 2025)
This article critically examines the conflict in Wadas Village as a representative case of legal and ecological tensions arising from the implementation of Indonesia’s National Strategic Projects. It interrogates how legal reasoning can be restructured to support justice in state-driven development projects that encroach upon local communities’ land, ecological security, and political rights. Employing a normative juridical method grounded in critical hermeneutics and socio-legal perspectives, the study analyzes constitutional norms, statutory regulations, gubernatorial decrees, and environmental planning laws. Findings reveal that procedural legality has often been used to legitimize state coercion, undermining participatory governance and spatial justice. The article argues for a transformative legal reasoning framework that incorporates ethical deliberation, legal listening, and principles such as Free, Prior, and Informed Consent (FPIC). It concludes that legal reform must reorient law toward substantive justice and democratic accountability, particularly in contested ecological landscapes.